Catalytic asymmetric (4 + 1) annulation of nitroalkenes with allylic acetates: stereoselective synthesis of isoxazoline N-oxides12. Issue 29 (12th July 2019) - Luo, Jinghua; Chen, Rongshun; Fan, Xia; Gong, Junyu; Han, Jie; He, Zhengjie
Abstract : A highly enantioselective catalytic asymmetric (4 + 1) annulation reaction of nitroalkenes and ammonium ylides is reported for the first time. Abstract : An asymmetric (4 + 1) annulation of α-nitro cinnamates with Morita–Baylis–Hillman (MBH) acetates catalyzed by α-isocupreine is reported. It provides chiral isoxazoline N -oxides in moderate to good yields with 88–99% ee, and represents the first catalytic asymmetric (4 + 1) annulation of activated nitroalkenes with in situ generated ammonium ylides. It also affords a practical and efficient access to chiral isoxazoline N -oxides.